The definition of family in the law versus social changes in Poland (Discourse of Law and Administration, 2021)
A family is a term deeply rooted in every-day language, and because of its basic and vital role for social life an obvious object of lawmakers’ interest. It is also a term which is defined differently, based on someone’s views and the needs of a particular regulation or branch of law. Its importance is also a practical matter, as one can grant certain rights to it or its members in different regulations and the differences between the definitions are about its subjects’ scope mostly, which brings us to the question: which subjects belong to one family? In this article the author presents different legislative approaches towards the definition of the family, starting with the constitutional ones, their variety, as well as international law ones, valid in Republic of Poland, and in regular regulation as well, especially in social and tax law. He tries to assess the adequacy of aforementioned definitions in terms of current social transformations in Poland and legal actions, as well as indicate pros and differences between the more traditional and more modern of them. Finally, he displays his idea of solving the aforementioned dilemmas, both in aspect of the plurality aspect, and worldview as well.
Keywords: family; legal definitions; the constitution; social welfare